Does the Tube Voltage Affect the Characterization of Coronary Plaques on 100- and 120-kVp Computed Tomography Scans. Issue 3 (May 2019) - Masuda, Takanori; Nakaura, Takeshi; Funama, Yoshinori; Sato, Tomoyasu; Okimoto, Tomokazu; Noda, Noritaka; Matsumoto, Yoriaki; Yamashita, Yukari; Imada, Naoyuki; Awai, Kazuo
Abstract : Objective: The aim of this study was to compare the diagnostic performance of 100- and 120-kVp coronary computed tomography (CT) angiography (CCTA) scans for the identification of coronary plaque components. Methods: We included 116 patients with coronary plaques who underwent CCTA and integrated backscatter intravascular ultrasound studies. On 100-kVp scans, we observed 24 fibrous and 24 fatty/fibrofatty plaques; on 120-kVp scans, we noted 27 fibrous and 41 fatty/fibrofatty plaques. We compared the fibrous and the fatty/fibrofatty plaques, the CT number of the coronary lumen, and the radiation dose on scans obtained at 100 and 120 kVp. We also compared the area under the receiver operating characteristic (ROC) curve of the coronary plaques on 100- and 120-kVp scans with their ROC curves on integrated backscatter intravascular ultrasound images. Results: The mean CT numbers of fatty and fatty/fibrofatty plaques were 5.71 ± 36.5 and 76.6 ± 33.7 Hounsfield units (HU), respectively, on 100-kVp scans; on 120-kVp scans, they were 13.9 ± 29.4 and 54.5 ± 22.3 HU, respectively. The CT number of the coronary lumen was 323.1 ± 81.2 HU, and the radiation dose was 563.7 ± 81.2 mGy-cm on 100-kVp scans; these values were 279.3 ± 61.8 HU and 819.1 ± 115.1 mGy-cm on 120-kVp scans. The results of ROC curve analysis identified 30.5 HU as the optimal diagnostic cutoff value for 100-kVp scans (area under the curve = 0.93, 95% confidence interval = 0.87–0.99, sensitivity = 95.8%, specificity = 78.9%); for 120-kVp plaque images, the optimal cutoff was 37.4 HU (area under the curve = 0.87, 95% confidence interval = 0.79–0.96, sensitivity = 82.1%, specificity = 85.7%). Conclusions: For the discrimination of coronary plaque components, the diagnostic performance of 100- and 120-kVp CCTA scans is comparable.